INNOVATION PERFORMANCE: ABSORPTIVE CAPACITY TO INCREASE PERFORMANCE IN SMALL AND MEDIUM-SIZED ENTERPRISES (SMES) (CASE STUDY: SMES IN MANADO) - Tulangow, Kezia C.; Massie, James D.D (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Performance innovation is becoming more and more important in order to create competitive advantage in this management environment especially in small and medium-sized enterprises (SMEs) that the speed of changes is getting faster and the lifecycle of product is being reduced. To improve the performance in SMEs, companies need to have absorption ability to utilize external knowledge and skills effectively. Such absorption ability is formed through interaction with internal and external resources of an organization and the characteristics of environment and so has important association with the results of performance innovation. The objectives of this research is to know the impact of exploratory learning, exploitative learning and transformative learning in absorptive capacity to Innovation Performance in Small and Medium-Sized Enterprises (SMEs). This research applied causal type with quantitative research method. Population of this study are 100 respondents from Small and Medium-Sized Enterprises in Manado. The Result indicate that exploratory learning, exploitative learning and transformative learning influence the innovation performance. Meanwhile, exploratory learning and transformative learning are insignificantly influence the innovation performance. As the recommendation, SMEs start to recognize the important of absorption ability in the future. In general, if acquiring new and a high level of knowledge, it should be reconstructed appropriately for our SMEs in Manado. Keywords: innovation performance, absorptive capacity, smes